Managing BRCA Mutation Carriers - B. Chagpar, Anees (Springer International Publishing : Imprint: Springer, 2017)
As there are a number of nuances in terms of how to manage mutation carriers (both with and without a concomitant diagnosis of breast cancer), this text provides a comprehensive, state-of-the art review of this field. It represents a valuable resource for a myriad of clinicians and healthcare personnel who interface with these patients. The text discusses the latest recommendations for genetic counseling and risk assessment, provides a framework for considering reducing risk in mutation carriers who do not present with a concomitant diagnosis of breast cancer, and finally elucidates the many considerations of managing a breast cancer patient with a BRCA mutation. The text presents a multidisciplinary approach gleaning insights from imaging, breast surgery, gynecology, plastic surgery, medical oncology, radiation oncology and psycho-oncology. Managing BRCA Mutation Carriers will be a useful resource for physicians and healthcare providers from a myriad of disciplines who manage BRCA mutation carriers. All chapters are written by experts in their fields and include the most up to date scientific and clinical information.
Keywords: Medicine.; Human genetics.; Oncology.; Pathology.; Surgical oncology.; elektronické knihy; electronic books